2014
DOI: 10.1097/pas.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Expressions Are Only Associated With MCPyV-positive Merkel Cell Carcinomas But Not With MCPyV-negative Ones

Abstract: Merkel cell carcinoma (MCC) is an aggressive neuroendocrine skin cancer, often associated with Merkel cell polyomavirus (MCPyV). Recently, immunoglobulin (Ig) expression was reported in MCC, thereby suggesting that B cells might be their cellular ancestors. We tested 30 MCCs (20 MCPyV-positive and 10 MCPyV-negative) using immunohistochemistry for the expressions of IgG, IgA, IgM, Igκ, Igλ, terminal desoxynucleotidyl transferase, paired box gene 5 (PAX5), octamer transcription factor-2 (Oct-2), and sex-determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…found that at least one immunoglobulin (IgG, IgA, IgM or Igκ) was expressed in MCPyV‐positive MCCs (14/20, 70%) and none in MCPyV‐negative MCCs. They found a higher tendency for Igκ mRNA expression (7/19) and IgH rearrangement (10/20, using PCR) in MCPyV‐positive than in MCPyV‐negative MCCs (0/10 and 2/10, respectively), thus suggesting a different immunoglobulin production pattern and pathogenesis between the two subtypes of MCC . Our results indicating that B‐cell clonality is usually absent in MCC support the observations by Zur Hausen et al ., who detected IgH and/or IgK rearrangement in only 3 of the 18 cases they analysed.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…found that at least one immunoglobulin (IgG, IgA, IgM or Igκ) was expressed in MCPyV‐positive MCCs (14/20, 70%) and none in MCPyV‐negative MCCs. They found a higher tendency for Igκ mRNA expression (7/19) and IgH rearrangement (10/20, using PCR) in MCPyV‐positive than in MCPyV‐negative MCCs (0/10 and 2/10, respectively), thus suggesting a different immunoglobulin production pattern and pathogenesis between the two subtypes of MCC . Our results indicating that B‐cell clonality is usually absent in MCC support the observations by Zur Hausen et al ., who detected IgH and/or IgK rearrangement in only 3 of the 18 cases they analysed.…”
supporting
confidence: 87%
“…Evidence from animal models suggests that epidermal/dermal stem cells might be the cellular origin of MCC. The recently formulated hypothesis of MCC originating from pro/pre‐B or pre‐B cells is supported by cell morphology, the consistent expression of early B‐cell lineage markers and the finding of clonal immunoglobulin chain rearrangement in MCC cells . Murakami et al .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Expression of B‐lymphoid lineage markers in MCC is frequent (Table ), including TdT and PAX5. These markers are recurrent in MCC in both primary cutaneous tumors and metastatic lymph nodes . Nearly, 90% of the tumors reported express PAX5 and 65% express TdT .…”
Section: Introductionmentioning
confidence: 98%
“…1). Darüber hi- positiven MZK nachgewiesen [35]. In unserer Testreihe von 21 MZK konnten wir bei fast allen MZK eine Expression der einen oder anderen Ig-Klasse oder Ig-Bestandteile feststellen.…”
unclassified